Tanggung Jawab Notaris Akan Perjanjian (Akta) Pinjam Nama (Nominee) Warga Negara Asing Dalam Kepemilikan Tanah Dan Bangunan - Ulyannuha, Dzurwatul; Ery Agus Priyono (LPPM Universitas Ekasakti Padang, 2024)
A nominee agreement made by a notary is actually a form of legal smuggling, which is used for the benefit of a foreign party. Basically, a nominee agreement provides all authority that may arise in relation to national land law which cannot be owned by foreign parties, which is then given to native residents as recipients of power of attorney. There are problems that arise, namely the applicable legal provisions relating to the making of a deed of borrowing a notary's name, the responsibility of a notary in making a Nominee deed for a land rights agreement between local residents and foreign nationals. This research uses a type of normative legal research and is analytical descriptive, where this research uses premier data as complementary data using data collection techniques carried out by means of literature study, as well as qualitative data analysis. Deeds of borrowing names or nominees are legally permissible, especially in shareholder agreements, however, unlike land ownership in the country, making deeds of borrowing names by a notary is an act of smuggling agrarian law and is prohibited by law. Based on Article 21 paragraph (1), Article 26 paragraph (2) of Law Number 5 of 1960 concerning Basic Agrarian Regulations, it is stated that a nominee agreement is an invalid agreement because it does not comply with statutory provisions. As a Notary there are three types of responsibility, namely civil legal responsibility, criminal legal responsibility and responsibility through the notary's code of ethics. The legal consequences that arise regarding the making of deeds of nomination, land ownership agreements between local residents and foreign nationals, namely that the nominal agreement is null and void.